Relações no Sertão da Amazônia (1790-1824): um rio e suas gentes no ensino de História - SOUZA, Elbia Cunha de (2021)
The present work highlights the Fronteira de Turiaçu that demarcated the boundary between the regions of Pará and Maranhão in the final years of the 18th century and the beginning of the 19th century and analyzes from scientific works by authors such as Sueny Diana de Souza, Flávio Gomes, among others, aspects of the social relations of the subjects who lived there in order to build a didactic resource to be used in elementary school in final years. Thus, the debate between the relationship between academic knowledge and school knowledge is necessary, since the proposal for the production of a didactic resource for the teaching of history will only be feasible based on the researches built in the academy and adapted to the school space. Thus, through the didactic resource proposed here, there are possibilities to study several concepts of History Teaching, as the aspects selected for this material allow to analyze through this border region the notions of power relations, notions of space, notions of source, subjects historical, social organization, territories and borders. Thus proposing updated knowledge and debated in the academy to arrive at the school, because it is believed in the potential of the themes and concepts of this region for daily exercise of the teacher and student, through the compiled organized in this didactic resource.